Badminton Smash Basic Training Model - Rahmat, Ade (INSPIREE: Indonesian Sport Innovation Review, 2021)
The  purpose  of  the study. This study aims to develop a basic training model for badminton Smash in badminton athletes in West Kalimantan. Materials and methods. The method used in this study is research and development modifying the Brog and Gal model. Results. The results of this study indicate that the badminton smash basic training model can be said to be valid from the study and assessment by experts. Conclusions. And the development of basic badminton smash training model is categorized as feasible to be used in badminton smash training because the developed smash model can be a smash training model that requires hand skills and strength, so the Badminton Smash Basic Training Model is recommended as a training model that can provide new nuances in apply a good smash.